(untitled) (Research, Society and Development, 2024)
Third molar surgeries in dental offices are routine interventions, which require professional skills to carry out, aiming to avoid complications both intra-operatively and post-operatively. Paresthesia of the inferior alveolar nerve is one of the complications that can occur after the extraction of third molars, given the proximity of the roots to the mandibular canal where this nerve is inserted. The inferior alveolar nerve is responsible for the sensitivity of the lips, chin and lower teeth. During surgical procedures this nerve can be compressed or injured, resulting in a tingling sensation, numbness and even loss of sensitivity, called paresthesia. Paresthesia can be partial or total depending on the severity of the injury and whether or not the condition can be reversed. The general objective of this research is to present the main diagnostic methods for this condition, the existing treatment techniques, as well as their effectiveness for the treatment of inferior alveolar nerve paresthesias after third molar extraction, through a narrative review of the literature. The literature investigated indicates that the diagnostic methods for paresthesia are made through clinical neurosensory testing, which are divided into mechanoceptive and nociceptive. Regarding treatments, if no conclusion has been reached about the ideal, the use of anti-inflammatories, antineuritics and vitamin B complex compounds in association with laser therapy are generally the most chosen.